The Characteristics of Intelligence Profile and Eye Gaze in Facial Emotion Recognition in Mild and Moderate Preschoolers With Autism Spectrum Disorder - He, Yuying; Su, Qi; Wang, Lan; He, Wenxiang; Tan, Chuanxue; Zhang, Haiqing; Ng, Manwa L.; Yan, Nan; Chen, Yanni (Frontiers in Psychiatry, 2019)
Childhood autism spectrum disorder (ASD) can easily be misdiagnosed, due to the nonspecific social and communicational deficits associated with the disorder. The present study attempted to profile the mental development and visual attention toward emotion among preschool children with mild or moderate ASD who were attending mainstream kindergartens. A total of 21 children (17 boys and 4 girls) diagnosed with mild or moderate ASD selected from 5,178 kindergarteners from the Xi’an city were recruited. Another group of 21 typically developing (TD) children who were matched with age, gender, and class served as controls. All children were assessed using the Griffiths Mental Development Scales–Chinese (GDS-C), and their social visual attention was assessed during watching 20 ecologically valid film scenes by using eye tracking technique. The results showed that ASD children had lower mental development scores in the Locomotor, Personal-Social, Language, Performance, and Practical Reasoning subscales than the TD peers. Moreover, deficits in recognizing emotions from facial expressions based on naturalistic scene stimuli with voice were found for ASD children. The deficits were significantly correlated with their ability in social interaction and development quotient in ASD group. ASD children showed atypical eye-gaze pattern when compared to TD children during facial emotion expression task. Children with ASD had reduced visual attention to facial emotion expression, especially for the eye region. The findings confirmed the deficits of ASD children in real life multimodal of emotion recognition, and their atypical eye-gaze pattern for emotion recognition. Parents and teachers of children with mild or moderate ASD should make informed educational decisions according to their level of mental development. In addition, eye tracking technique might clinically help provide evidence diagnosing children with mild or moderate ASD.